A Comprehensive Study on Empowering High School Students for Career Success in a Government School in Sharjah - Mona Abumady (2025)
This qualitative research examines the factors that influence career empowerment among high school students in a government institution in Sharjah, UAE. It evaluates the efficacy of existing career guidance programs, the extent of students’ awareness of career pathways, and the influence of educational institutions on their aspirations. The study proposes strategies to improve students’ career readiness by identifying challenges in current guidance practices and conducting document analysis, interviews, and focus groups. The significance of career counseling, skill development, and informed decision-making in enabling students to select suitable universities and prospective professions is underscored by the results. The research endeavors to offer policymakers, educators, and stakeholders actionable insights to enhance career guidance programs, thereby promoting more informed career choices and self-efficacy among students.